Ответы и объяснения

Лучший Ответ!
2013-01-21T13:29:10+04:00

y=\frac{2}{7}x^3\sqrt{x}-\frac{4}{11}x^5\sqrt{x} = \frac{2}{7}x^{\frac{7}{2}}-\frac{4}{11}x^{\frac{11}{2}} \\ y'=x^{\frac{5}{2}}-2x^{\frac{9}{2}} =x^{2.5}(1-2x^2)

 

y' = (x^2 + 2x + 2)'e^{-x}+(x^2 + 2x + 2)(e^{-x})'=(2x+2)e^{-x}-(x^2 + 2x + 2)e^{-x} = -x^2e^{-x}

 

y' = (\sin (\ln x))'(\cos (\ln x)) +(\sin (\ln x))(\cos (\ln x))' = \\ = \frac{\cos^2(\ln x)}{x} - \frac{\sin^2(\ln x)}{x} = \frac{\cos(2\ln x)}{x}

 

y'(\pi / 2) = 5 \cos(\pi/2) - 3\sin(\pi/2) = -3

уравение касательной - y = -3x + C1

уравнение нормали - y = 1/3x + C2

в точке \pi / 2 функция принимает значение 5, значит

C1=5+\frac{3\pi}{2}

C2 = 5 - \frac{\pi}{6}